(untitled) (Web of Teachers: Inderscience Research, 2024)
Translation has always played a pivotal role in shaping world literature, acting as a bridge that connects diverse cultures and languages. In an increasingly globalized world, the importance of translation extends beyond mere linguistic conversion, contributing to cross-cultural understanding and the exchange of ideas. This article explores the significance of translation in world literature, highlighting its historical evolution, challenges, and the impact it has had on the development of literary traditions. It also delves into modern trends in translation, including technological advancements, the rise of literary translation as a profession, and the role of translation in the global dissemination of literature. Through this exploration, the article underscores the continuing relevance of translation in fostering cultural dialogue and enriching the literary landscape.